Ultrafast and ultrastable high voltage cathode of Na2+2xFe2-x(SO4)3 microsphere scaffolded by graphene for sodium ion batteries. (10th February 2019) - Liu, Xiaohao; Tang, Linbin; Xu, Qunjie; Liu, Haimei; Wang, YongGang
Abstract: Na2+2x Fe2-x (SO4 )3 is considered a promising cathode material for advanced sodium ion batteries with higher energy density due to its advantage of high-voltage, earth-abundant elements material and low-cost. However, strongly impeded by its fatal environmental sensitivity and low electronic conductivity, the NFS usually shows unsatisfactory electrochemical performance. Herein, a facile synthesis of microspherical NFS@reduced graphene oxide composites are synthesized through spray-drying method. The well-designed microspherical NFS@rGO with confined NFS nanocrystal in the three-dimensional graphene framework exhibits superb electronic and ionic conductivity as well as structural stability. The NFS@rGO composites show outstanding electrochemical properties: high sodium storage capacity (99 mAh g −1 at 0.1 C), superior rate performance (78 mAh g −1 at 60 C and even up to 72 mAh g −1 at 80 C), ultralong cycling stability (80.8% capacity retention after 2000 cycles at 30 C). The excellent performance makes the NFS@rGO material a prospective electrode candidate for large-scale SIBs. Graphical abstract: Image 1 Highlights: The NFS@rGO was successfully prepared through a facile spray-drying method. The robust 3D graphene skeleton ensures NFS@rGO structural stability. The 3D highly conductive graphene network boost the electronic conductivity. The NFS@rGO demonstrates ultrafast and ultralong-term cycling.